A retrospective study of histopathological exam reports of appendix in appendectomies performed at a teaching hospital in Dehradun - Kumar, Ajay; Altamash, Syed; Kumar, Amitav; Singhal, Pradeep; Bijalwan, Anurag (International Surgery Journal, 2020)
Background: Appendix is a vestigial organ in human body. Inflammation of appendix is termed as appendicitis. The diagnosis of appendicitis still holds dilemma amongst surgeons leading to negative appendectomies on one hand and appendicular perforation on the other hand of therapeutic spectrum. Judicial patient selection for appendectomy and follow up histopathological examination for incidental findings is the cornerstone in management of appendicitis. The current study aims to assess the demographic and histopathological findings of all the appendectomies occurring within study period at our center. Methods: It was a retrospective study over two years done in a teaching hospital of Dehradun. Hospital records were retrieved from medical records department and looked for histopathological findings, demographic details and intervention. The data was analyzed in SPSS version 23. Qualitative and quantitative data were expressed in proportions and mean respectively. T-test was applied for comparison. Results: About 2/3rd of participants were males. The peak age was 20-30 years. 100 underwent open appendectomy and 45 had lap appendectomy. Commonest histopathological exam finding was acute appendicitis (46.2%) followed by peri appendicitis (40%) and resolving appendicitis (28.9%). One specimen had tubercular appendix. There were no negative appendectomies. Conclusions: Elective appendectomy in patients satisfying clinical, lab and radiological criteria can reduce negative appendectomies. Histopathological examination of appendix still holds a valid role for any incidental findings requiring further management.